StM171, a Stenotrophomonas maltophilia Bacteriophage That Affects Sensitivity to Antibiotics in Host Bacteria and Their Biofilm Formation - Ghadeer Jdeed; Vera Morozova; Yuliya Kozlova; Artem Tikunov; Tatyana Ushakova; Alevtina Bardasheva; Andrey Manakhov; Maria Mitina; Elena Zhirakovskaya; Nina Tikunova (Viruses, 2023)
Stenotrophomonas maltophilia mainly causes respiratory infections that are associated with a high mortality rate among immunocompromised patients. S. maltophilia exhibits a high level of antibiotic resistance and can form biofilms, which complicates the treatment of patients infected with this bacterium. Phages combined with antibiotics could be a promising treatment option. Currently, ~60 S. maltophilia phages are known, and their effects on biofilm formation and antibiotic sensitivity require further examination. Bacteriophage StM171, which was isolated from hospital wastewater, showed a medium host range, low burst size, and low lytic activity. StM171 has a 44kbp dsDNA genome that encodes 59 open-reading frames. A comparative genomic analysis indicated that StM171, along with the Stenotrophomonas phage Suso (MZ326866) and Xanthomonas phage HXX_Dennis (ON711490), are members of a new putative Nordvirus genus. S. maltophilia strains that developed resistance to StM171 (bacterial-insensitive mutants) showed a changed sensitivity to antibiotics compared to the originally susceptible strains. Some bacterial-insensitive mutants restored sensitivity to cephalosporin and penicillin-like antibiotics and became resistant to erythromycin. StM171 shows strain- and antibiotic-dependent effects on the biofilm formation of S. maltophilia strains.